Women’s multifaceted citizenship in rural Uganda : an exploration of identity, belonging and spaces of participation - Del-Castillo-Munera, Laura (2021)
This research studies women’s citizenship practice exploring their daily interactions and participation in the rural districts of Kiboga and Namutumba in Uganda. Analyzing women’s daily interactions in the private and public domains provides new perspectives of women’s contribution to citizenship at the grassroots. This study joins the contestations of the contemporary scholarship of citizenship by first proposing a notion of multifaceted citizenship that acknowledges the dynamism of citizenship, that citizenship is context dependent and that relationships and daily practices are a crucial part of it; second by exploring feminist perspectives of citizenship and its contribution of an inclusive model of citizenship while exploring the concepts of identity, belonging and spaces of participation and their implication on women’s citizenship. This research provides perspectives on how lived citizenship is practiced among women in the context of rural Uganda by addressing three research questions. First, how women construct their identities and those of their community through the spaces of participation? Second, how women’s participation promote the reproduction of belonging in their community? Third, how are women’s identities and belongings manifested differently based on the spaces of participation? This research interest arises from the current analytical work in citizenship and civil society in Eastern Africa conducted by the Civil Society and Citizenship in Development (CitDe) research group. This Thesis analyzes 50 qualitative individual interviews conducted to women in the rural districts of Kiboga and Namutumba in Uganda. Data were collected by Ugandan researchers for the Growth into Citizenship in Civil Society Encounters (GROW) project and were analyzed by this researcher using qualitative content analysis and the coding software ATLAS.ti. Findings revealed first, women’s daily interactions, self-acceptance, recognition and different roles women play in their community is what seems to contribute to identity construction. Second, participating in groups, group and community membership, emotional and relational bonds and the level of attachment to each group is what seems to promote women’s reproduction of belonging in their community. Finally, interactions and participations that enable women to construct their identities and reproduce their belongings occur in physical spaces that are public or private; findings suggest that identities and belongings can manifest differently based on the different spaces women participate in. In conclusion, women’s active participation in the private and public domains are the daily interactions that contribute to women’s exercise of citizenship. This study recommends to continue investigating lived citizenship without gender blindness in any research —considering both female and males and other gender identifications—at the grassroots in Africa and beyond.